2004
DOI: 10.1016/j.coi.2004.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and loss of virus-specific CD8+ T-cell memory

Abstract: CD8(+) T-cell memory to viruses is stable in the absence but volatile in the presence of other infections. Apoptotic events that occur early in acute infections delete pre-existing memory T cells, leaving the host with reduced memory (except for cross-reactive responses) to previously encountered viruses. Apoptotic events also silence the acute immune response, leaving the host with a residual population of memory T cells. Persistent infections can induce apoptotic deletions of memory T cells that are specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
1
20
1
Order By: Relevance
“…Therefore, it is unlikely that infection with CMV would impair EBV-specific T cell responses. Our findings do not corroborate the data retrieved from mice studies where competition between memory T cells was shown (11)(12)(13)(14), especially because CMV will give rise to latent infection and these mice studies showed that the attrition of memory T cells was most prominent upon infection with a persistent virus (15). We conclude from our data that the size of the human memory T cell pool is not so strictly regulated that the entrance of new cells leads to the disappearance of others.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Therefore, it is unlikely that infection with CMV would impair EBV-specific T cell responses. Our findings do not corroborate the data retrieved from mice studies where competition between memory T cells was shown (11)(12)(13)(14), especially because CMV will give rise to latent infection and these mice studies showed that the attrition of memory T cells was most prominent upon infection with a persistent virus (15). We conclude from our data that the size of the human memory T cell pool is not so strictly regulated that the entrance of new cells leads to the disappearance of others.…”
Section: Discussioncontrasting
confidence: 55%
“…Several studies in mice have shown that infection with a new virus, and consequent emergence of an additional population of memory cells, results in permanent loss of pre-existing memory T cells against unrelated pathogens (11)(12)(13). In this way, the overall size of the memory T cell pool remains relatively constant, and memory T cells have to compete for physical space and/or homeostatic cytokines (14). There appears to be a difference between T cells specific for viruses that are cleared by the host and viruses that persist.…”
Section: Differential Usage Of Cellular Niches By Cytomegalovirus Vermentioning
confidence: 99%
“…61,63,64 Many viral infections in mouse and human induce a substantial loss in lymphocyte and leukocyte numbers in the early stages of infections. 65 A substantial loss in CD8 and CD4 T cell number during the first 5 days of LCMV infection parallels the levels of type 1 IFN production, does not occur in type 1 IFN receptor ko mice, 66 is blocked by antibody to type 1 IFN 67 and is mimicked by IFN-inducing toll receptor agonists, such as poly I:C. 66 The apoptotic loss of memory occurs prior to cell division. 63,66,68 An in silico virtual immune system model, IMMSIM, which unlike a biological system can selectively turn off either active or passive attrition, predicted that without the active attrition and apoptosis of memory T cells early in infection, crossreactive T cells might overwhelmingly dominate the response to an infection.…”
Section: Heterologous Immunity and T Cell Crossreactivitymentioning
confidence: 99%
“…One intriguing possibility is that SL9 provokes a cross-reactive memory T cell response to one or more common pathogen(s). This would also explain why SL9 reactivity is rare in acute infection, when cross-reactive memory cells are driven into apoptosis (heterologous immunity) (64). From the perspective of vaccine design, it implies that it may be difficult to induce useful SL9 responses with the native Gag protein in HLA-A2 ϩ people.…”
Section: Discussionmentioning
confidence: 99%